Relationship of Biometric Attendance System with Performance, Job Related Stress and Satisfaction of University Teachers in Pakistan - Abid Ali (Liberal Arts and Social Sciences International Journal, 2018)
The main target of this research study is to dig-out the impact of biometric attendance on teachers’ performance at Hazara University. A self-administered structured questionnaire is developed for data collection. A sample of 150 employees are chosen from the targeted population through stratified random sampling. The collected data is collated, coded, and punched in the SPSS for descriptive and inferential analysis. The results point out that 67% of those informants are male, while 33% are females. The highest number, 58% of employees are in Grade-18, and only 5% employees are in Grade-21. Further, it shows that 88% participants are agreed to the installation of biometric attendance system. However, 87% respondents agreed that biometric system ensures teachers attendance on time. Moreover, correlation analysis results indicate that biometric system has a strong positive significant relationship with employees’ attendance and employees’ performance. But it has a significant negative relationship with job-related stress. Alongside, by independent sample T-test, gender differences are found that females are more in job-related stress than male due to the biometric system. The study concludes that biometric system has a high-level significant influence on the teachers’ attendance schedule and their performance. Further, the study recommends the application of biometric attendance system in academia, it will, in turn, improve and ensure the performance level of employees.